The Philippines in 1987 politics of survival? - Aquino, Belinda A. (1987)
The year 1987 was a critical one for the Aquino administration as it tried to consolidate the gains it made the year, before, and as it continued its efforts towards redemocratization and normalization. However, its stability has been seriously threatened by a number of events including the bloody August 28 coup attempt, the collapse of the ceasefire talks with the National Democratic Front and the proliferation of right-wing vigilante groups. But the moral leadership of President Aquino and the people's response to her call for national unity may save the nation from falling to the hands of the extremists from both the left and from the right.
Keywords: Aquino administration; Philippines -- Politics and government; Philippines -- History -- Revolution, 1986